Implementasi HACCP dan SSOP dalam Menjamin Kualitas Produk di Industri Pangan UMKM. Narrative Literature Review - Bimo Kuncoro Jati; Putri Viona Amalia; Sheryl Candra Sasi (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
Food safety is a critical issue in the food industry, as each stage of production poses potential hazards that may reduce product quality and endanger consumer health, particularly in micro, small, and medium enterprises (MSMEs). Inadequate sanitation practices and weak process control remain major causes of food contamination. This study aims to examine the effectiveness of implementing Hazard Analysis Critical Control Point (HACCP) and Sanitation Standard Operating Procedures (SSOP) in ensuring food quality and safety based on previous research findings. The study employed a Narrative Literature Review approach with qualitative analysis through document review and content analysis of relevant scientific articles published between 2015 and 2025. The literature was analyzed to identify HACCP and SSOP implementation practices, types of food industries, hazard control measures, and challenges in their application. The results indicate that consistent implementation of HACCP and SSOP is effective in reducing microbiological contamination risks, improving product quality, and enhancing production processes. However, several obstacles remain, including limited sanitation facilities, low worker discipline, weak documentation systems, and insufficient internal supervision, particularly among MSMEs and online food businesses. It can be concluded that HACCP and SSOP are fundamental pillars of food safety management systems, yet their effectiveness strongly depends on human resource commitment, hygienic work culture, and continuous training and facility support. Therefore, strengthened assistance, capacity building, and collaboration among stakeholders are essential to achieve effective and sustainable food safety implementation.